2022
DOI: 10.1111/inr.12756
|View full text |Cite
|
Sign up to set email alerts
|

Alleviating psychological symptoms in nurses during disease outbreaks: An integrative review

Abstract: AimTo explore interventions and coping strategies used to treat the psychological symptoms associated with compassion fatigue among nurses.BackgroundThe rapid transmission of infectious diseases (e.g., COVID‐19) has put nurses, around the world, at high risk of developing profound psychological health issues due to compassion fatigue. If unrelieved, compassion fatigue can lead to catastrophic psychological symptoms such as depression, stress, anxiety, and insomnia, negatively impacting patient care. This neces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Infectious disease pandemics entail the global spread of an emerging viral disease, while epidemics are defined as the spread of viral diseases over specific countries or continents. The globe has witnessed several infectious diseases' outbreaks, including Ebola, SARS and MERS (Hawsawi, 2022). Respiratory infectious pandemics and epidemics are particularly virulent given their spread via droplets and interpersonal contact (Fernandez et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Infectious disease pandemics entail the global spread of an emerging viral disease, while epidemics are defined as the spread of viral diseases over specific countries or continents. The globe has witnessed several infectious diseases' outbreaks, including Ebola, SARS and MERS (Hawsawi, 2022). Respiratory infectious pandemics and epidemics are particularly virulent given their spread via droplets and interpersonal contact (Fernandez et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…It can lead to medical errors, deterioration of relationships with co-workers and patients, and low work satisfaction and quality of care (Delle Donne et al, 2023). In times of infectious disease outbreaks, nurses are significantly vulnerable to developing several acute or chronic psychological symptoms of CF, including insomnia, fatigue, depression, and anxiety, which impact their health and patient care (Hawsawi, 2022).…”
Section: Nurses and Physiciansmentioning
confidence: 99%
“…31,32 Also, it is reported that coping strategies such as relaxation strategies, neutralizing emotional trauma, enhancing nurses' preparedness for confronting disasters, and educating nurses about coping strategies to manage their psychological issues were used to treat the psychological symptoms associated with compassion fatigue among nurses. 33 Considering the prevalence and impact of compassion fatigue on nurses' well-being and the quality of patient care, it is crucial to continue investigating effective coping strategies and support mechanisms. By understanding the factors that contribute to compassion fatigue and identifying successful interventions, healthcare organizations can proactively implement measures to address compassion fatigue among nurses during the COVID-19 pandemic and other challenging situations.…”
Section: Introductionmentioning
confidence: 99%
“…31,32 Also, it is reported that coping strategies such as relaxation strategies, neutralizing emotional trauma, enhancing nurses’ preparedness for confronting disasters, and educating nurses about coping strategies to manage their psychological issues were used to treat the psychological symptoms associated with compassion fatigue among nurses. 33…”
Section: Introductionmentioning
confidence: 99%